Conceptual Framework for Digital Transformation of Islamic Religious Education: Integrating Technology Acceptance Model, Digital Competence, and Pedagogy - Endah Rahmayanti; Wasehudin; Yahdinil Firda; Itang; Deni Iriyadi; Fitri Hilmiyati (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2026)
learning strategies, particularly in Islamic Religious Education (PAI). This paper aims to comprehensively examine the theoretical basis for developing a digital technology-based PAI teacher learning strategy model to improve the effectiveness and quality of learning. The discussion focuses on three main theoretical pillars: the Technology Acceptance Model (TAM) to analyze the perceived ease and usefulness of technology, the theory of teacher digital competence as a foundation for educator professionalism, and the theory of Digital Pedagogy relevant to the characteristics of students as a digital generation. Through a literature review, this paper explores how the integration of multimedia, online-based learning, and digital pedagogy can improve the effectiveness and quality of learning. Platform Interactive learning can address the digital divide and strengthen students' learning motivation without compromising Islamic spiritual values. The study's findings confirm that the success of Islamic Education's digital transformation depends not only on the availability of infrastructure but also on a shift in teachers' pedagogical paradigms from traditional (teacher-centered) models to modern, interactive, collaborative, and value-oriented learning (values-based learning). This paper recommends the need strategic model framework to realize the profile of moderate and digitally literate Muslim students.